Regulation of Criminal Acts of Narcotics Abuse in the Narcotics Law - Prabowo, Dedi Singgih; Mujito, Mujito; Darmawan, Didit (Metromedia, 2024)
Drug abuse has become one of the most serious problems in Indonesia, posing a threat to public health, social stability, and state security. This study aims to explore the regulation of drug abuse in Indonesia's Narcotics Law, identify its strengths and weaknesses, and analyze the implementation of the regulation in drug eradication efforts. With a normative juridical approach based on literature studies, this research reviews various aspects of the law, ranging from criminal sanctions, rehabilitation mechanisms, to prevention and law enforcement policies. The findings show that although regulations have been comprehensively drafted, there are significant challenges in their implementation, such as disparities in law enforcement, lack of coordination between institutions, and lack of attention to rehabilitation programs for drug users. This study proposes several recommendations to strengthen policy effectiveness, including revision of regulations and strengthening the capacity of law enforcement officials. Thus, this study contributes to the development of more effective policies in dealing with the drug problem in Indonesia.